Control Contable De La Empresa “Comercial Meggy” - Vera Vera, Clara Yumira (2020)
The present investigation was carried out at the Comercial Meggy company in the Canton Vinces, to find out what are the difficulties that the company shows due to the lack of accounting control, where the problems in the accounting processes carried out by the company were identified, so these they are not executed in accordance with the entity's accounting procedures manuals. According to the analysis made to the company, it was observed that it does not keep proper accounting. At the time of evaluating each of the processes, deficiencies were found, which negatively affect the entity. The commercial has the obligation to keep accounting, but only complies with its tax obligations, without keeping a record of its transactions and without issuing financial statements, therefore, the accounting area does not have this type of instrument for decision-making and At the same time, you cannot know if you have enough liquidity to face your short-term debts or if you are only financing yourself with third-party debts. It was also identified that the entity erroneously registers the expenses according to their nature, therefore, they are not classified